Between inspection and care. The look on the bodies in the programs of affectivity and sexuality in Costa Rica - Vindas Sánchez, Daniel (2019)
This paper intends a theological and philosophical analysis of the Affective and Sexuality Programs of the Ministry of Costa Rican Public Education. First, it seeks to understand the archaic grip that influences this form of sexual ethics, through the figure of the pedagogue, the abbot and the doctor. One of the central hypotheses of this work is that these Programs largely participate in a rule without a monastery, within an ethical scheme that resides between inspection and self-care, a paradox that has to be confronted in these guides.